Ultrasound Pulsed-Wave Doppler Detects an Intrathecal Location of an Epidural Catheter Tip: A Case Report. Issue 7 (1st April 2018) - Elsharkawy, Hesham; Saasouh, Wael; Patel, Bimal; Babazade, Rovnat
Abstract : Currently, no gold standard method exists for localization of an epidural catheter after placement. The technique described in this report uses pulsed-wave Doppler (PWD) ultrasound to identify intrathecal location of an epidural catheter. A thoracic epidural catheter was inserted after multiple trials with inconclusive aspiration and test dose. Ultrasound PWD confirmed no flow in the epidural space and positive flow in the intrathecal space. A fluid aspirate was positive for glucose, reconfirming intrathecal placement. PWD is a potential tool that can be used to locate the tip of an epidural catheter. Abstract : Supplemental Digital Content is available in the text.